Analysis of Factors Affecting the Development of Children of Toddler Ages Assessed from History of Infection Diseases, Nutritional Status and Psychosocial Stimulation in Ponorogo Regency - Rischa Devi Hayuningtyas; Siti Farida Noor Laila; Nurwijayanti Nurwijayanti (Journal for Quality in Public Health, 2020)
Child development is the result of maturation of organs, especially the central nervous system. Development occurs throughout life consisting of several stages, one of which is toddler. The toddler age occurs from 1 to 3 years old, where child development occurs very rapidly and is a golden period in children. Success in mastering developmental tasks at toddler age requires a strong foundation during the period of growth and development. This study aims to analyze factors that influence the development of toddler age children in terms of history of infectious diseases, nutritional status and psychosocial stimulation in Ponorogo Regency. The research design used is quantitative research with a cross sectional approach with a propopotional stratified random sampling method. The samples were taken as many as 302 mothers and toddler age children in the Ponorogo regency. The test used in this study was ordinal regression. The results showed the effect of value infectious disease history variable (wald = 10,356, P value = 0,001, estimate = 1,386), nutritional status value (wald = 810,900, P value = 0,000, estimate = 13,303). The value of psychosocial stimulation (Wald = 7,952, P value = 0,005, estimate = 1,309). at α = 0.05, the influence of the development of toddler age children is influenced by a history of infectious diseases, nutritional status and pshycosocial stimulation significantly. The development of toddler age in Ponorogo Regency is influenced by a history of infectious diseases, nutritional status and psychosocial stimulation. It is recommended that mothers pay more attention to adequate nutritional intake so that toddler-age children are not susceptible to infectious diseases. And supported psychosocial stimulation for optimal development. Nutritional status is the most dominant factor contributing to the development of toddler age children